2003
DOI: 10.1136/oem.60.7.516
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer in heavy equipment operators and truck drivers with diesel exhaust exposure in the construction industry

Abstract: Background: Several studies indicate that truck drivers have an increased risk of lung cancer, but few studies have examined lung cancer risk in heavy equipment operators. Workers in both occupations are exposed to diesel exhaust. Aims: To examine the incidence and mortality from lung cancer among truck drivers and among drivers of heavy vehicles. Methods: A computerised register of Swedish construction workers participating in health examinations between 1971 and 1992 was used. Male truck drivers (n = 6364) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 19 publications
3
35
1
Order By: Relevance
“…A total of 6364 male truck drivers and 14,364 drivers of heavy construction vehicles were investigated as DE-exposed groups. Altogether, 119,984 carpenters and electricians formed the reference group (J€ arvholm & Silverman 2003). Each worker was followed from his first health examination between 1971 and early 1993 to 31 December 1995.…”
Section: Description Of the Study And Authors' Main Resultsmentioning
confidence: 99%
“…A total of 6364 male truck drivers and 14,364 drivers of heavy construction vehicles were investigated as DE-exposed groups. Altogether, 119,984 carpenters and electricians formed the reference group (J€ arvholm & Silverman 2003). Each worker was followed from his first health examination between 1971 and early 1993 to 31 December 1995.…”
Section: Description Of the Study And Authors' Main Resultsmentioning
confidence: 99%
“…The meta-analysis included studies from Canada (Aronson et al 1996;Band et al 1999) the USA (Brown and Delzell 2000;Krstev et al 1998a) and Europe (Zeegers et al 2004;Sharma-Wagner et al 2000;Jarvholm and Silverman 2003). Five studies reported data on incidence of prostate cancer (Aronson et al 1996;Band et al 1999;Krstev et al 1998a;Zeegers et al 2004;Sharma-Wagner et al 2000) and three on mortality (Brown and Delzell 2000;Krstev et al 1998b;Jarvholm and Silverman 2003).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 98%
“…Five studies reported data on incidence of prostate cancer (Aronson et al 1996;Band et al 1999;Krstev et al 1998a;Zeegers et al 2004;Sharma-Wagner et al 2000) and three on mortality (Brown and Delzell 2000;Krstev et al 1998b;Jarvholm and Silverman 2003). The cohort studies used population referent groups, while the case-control studies used population and/or other cancer controls.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 98%
“…Nonetheless, exposure to these agents has been well controlled in developed countries in the last decades (1). Additionally, in epidemiologic studies, exposure to diesel exhaust was also demonstrated to induce LC in truck drivers (58,59), railroad workers (60), and operators of heavy construction equipment (61). More recently, exposure to new technologies included in the environment and workplace such as sandblasting jean workers and hydraulic fracturing (fracking) have introduced new hazards that may lead to the development of occupational diseases including LC (62).…”
Section: Occupational Exposurementioning
confidence: 99%